2014
DOI: 10.1186/1743-422x-11-109
|View full text |Cite
|
Sign up to set email alerts
|

Comparative quantitative monitoring of rabbit haemorrhagic disease viruses in rabbit kittens

Abstract: BackgroundOnly one strain (the Czech CAPM-v351) of rabbit haemorrhagic disease virus (RHDV) has been released in Australia and New Zealand to control pest populations of the European rabbit O. cuniculus. Antigenic variants of RHDV known as RHDVa strains are reportedly replacing RHDV strains in other parts of the world, and Australia is currently investigating the usefulness of RHDVa to complement rabbit biocontrol efforts in Australia and New Zealand. RHDV efficiently kills adult rabbits but not rabbit kittens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…In contrast, RHDV can be transmitted both orally by fomites or direct contact between rabbits (26), and passively via insect vectors, with the latter likely responsible for the escape of RHDV from quarantine in 1995 (45). While fomite/contact transmission is likely to play an important role in transmission during virus outbreaks (46), long distance transmission of RHDV occurs through flies that scavenge on decomposing carcasses, or fresh carcasses opened by predators, and then transmit the virus passively by landing on mucous membranes of rabbits directly, or by leaving faeces or regurgita on pasture that is subsequently ingested by rabbits (45, 47, 48). Hence, MYXV requires vectors to bite a live, diseased animal.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, RHDV can be transmitted both orally by fomites or direct contact between rabbits (26), and passively via insect vectors, with the latter likely responsible for the escape of RHDV from quarantine in 1995 (45). While fomite/contact transmission is likely to play an important role in transmission during virus outbreaks (46), long distance transmission of RHDV occurs through flies that scavenge on decomposing carcasses, or fresh carcasses opened by predators, and then transmit the virus passively by landing on mucous membranes of rabbits directly, or by leaving faeces or regurgita on pasture that is subsequently ingested by rabbits (45, 47, 48). Hence, MYXV requires vectors to bite a live, diseased animal.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the mechanism of action of nitazoxanide against influenza viruses have shown that the drug blocks maturation of the viral hemagglutinin at the post-translational stage (Rossignol et al, 2009a). The drug had no effect on the other glycoprotein, neuraminidase, the target of oseltamivir and zanamivir, or the M2 protein, the target of amantadine, and it had no effect on viral infectivity, adsorption or entry into target cells (La Frazia et al, 2013;Rossignol et al, 2009a;Shi et al, 2014).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…1 A vaccine designed to protect against RHD (Cylap®, Fort Dodge Cyanamid, USA) was registered for use in Australia in late 1995. 6 This study investigates the efficacy of the Cylap® RHD vaccine in rabbits exposed to very high doses of the K5 and v351 strains of RHDV. In common with many other commercial vaccines, there is little efficacy data in the peer-reviewed scientific literature.…”
mentioning
confidence: 99%